2018
DOI: 10.1097/hjh.0000000000001533
|View full text |Cite
|
Sign up to set email alerts
|

Circadian hemodynamics in men and women with high blood pressure

Abstract: Overall, these findings indicate that blunted night-time BP dipping is associated with impairment of the systemic vasodilation that is characteristic of the night-time sleep period and is especially prominent among African-Americans. In the context of high BP, these findings suggest that nondipping may be a manifestation, or marker, of more advanced vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 45 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…There are some important differences in diagnosis, clinical course, end-organ damage and complications, prognosis, clinical management, and treatment among different subtypes of hypertension [2,[17][18][19]. Recently, patients with dipping and nondipping patterns of hypertension have drawn the utmost attention of the researchers [20,21]. The most important reason for the researchers' interest is the presence of growing evidence about the higher incidence of target organ damages like stroke, myocardial hypertrophy and infarction, arrhythmia, and heart failure in patients with non-dipper hypertension [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…There are some important differences in diagnosis, clinical course, end-organ damage and complications, prognosis, clinical management, and treatment among different subtypes of hypertension [2,[17][18][19]. Recently, patients with dipping and nondipping patterns of hypertension have drawn the utmost attention of the researchers [20,21]. The most important reason for the researchers' interest is the presence of growing evidence about the higher incidence of target organ damages like stroke, myocardial hypertrophy and infarction, arrhythmia, and heart failure in patients with non-dipper hypertension [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the prominent vascular HP described here in healthy normotensive AAs may be among the earliest precursors to the development of hypertension in this ethnic group. Recent studies have suggested that the greater prevalence of hypertension observed in AAs may reflect a larger underlying pattern of vascular remodelling, by demonstrating (i) that total peripheral resistance was positively associated with minimal forearm vascular resistance, an index of vascular hypertrophy, among AAs, but not Whites, with elevated blood pressure (Hill, Sherwood, Blumenthal, & Hinderliter, 2016), and (ii) that in a sample of individuals with undiagnosed, untreated hypertension, AAs exhibited a blunted night-time BP dipping which was accompanied by an attenuated fall in total peripheral resistance compared with Whites (Sherwood, Hill, Blumenthal, & Hinderliter, 2018). The present findings in healthy normotensive young adults indicate statistically reliable higher values of resting diastolic BP in AAs, while no statistically reliable ethnic differences are observed in resting measures of MAP, systolic BP, cardiac output and total peripheral resistance although they were in the expected direction.…”
Section: Discussionmentioning
confidence: 99%
“…SVR also has been shown to play a stronger role in diurnal BP regulation among African Americans relative to European Americans [16]. Moreover, recent evidence has further shown that the well-known non-dipping phenomenon in nighttime BP, which is also more common among African Americans and is associated with elevated CVD morbidity and mortality risk, also is characterized by a corresponding blunted decline in nighttime SVR [17]. Importantly, research examining the role of psychosocial stress in CVD risk has consistently revealed that African Americans tend to exhibit exaggerated or enhanced vasoconstrictive, and/or impaired vasodilatory responses to a range of behavioral and psychological stressors [14,15].…”
Section: Taking a Closer Look At Autonomic (Im) Balancementioning
confidence: 99%